Ghosts - or the (Nearly) Invisible Spectral Phenomena in Literature and the Media - Schenkel, Elmar; Fleischhack, Maria (Peter Lang International Academic Publishers, 2016)
In this volume, ghost stories are studied in the context of their media, their place in history and geography. From prehistory to this day, we have been haunted by our memories, the past itself, by inklings of the future, by events playing outside our lives, and by ourselves. Hence the lure of ghost stories throughout history and presumably prehistory. Science has been a great destroyer of myth and superstition, but at the same time it has created new black boxes which we are filling with our ghostly imagination. In this book, literature from the Middle Ages to Oscar Wilde and Neil Gaiman, children's stories, folklore and films, ranging from the Antarctic and Russia to Haiti, are covered and show the continuing presence of spectral phenomena.
Description based on print version record.
KU Select 2017: Backlist Collection
Keywords: Literary Criticism / Semiotics & Theory; Literature -- History and criticism; Electronic books